ANALISIS KONTRIBUSI RETRIBUSI PARKIR, PAJAK REKLAME, DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA BADAN PENDAPATAN DAERAH KABUPATEN DELI SERDANG - Pulungan, Khairul Anwar; Miranda , Kiki (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2025)
PAD is all regional revenues originating from regional original economic sources. PAD is separated into, namely; regional taxes, regional levies, results of regionally-owned companies, results of separated regional wealth management, other legitimate PAD. One of the sources of regional original income is levies and local taxes. The purpose of this study was to determine and analyze the contribution of parking levies, advertisement taxes and restaurant taxes in increasing local revenue in Deli Serdang Regency. This research was conducted at the Regional Revenue Agency (BAPENDA) office of Deli Serdang Regency. The data analysis method used is quantitative research with a descriptive approach. The data collection technique in this research is the documentation technique, which is done by studying, classifying, identifying and collecting data from each variable. The results of the research analysis of the contribution of parking levies, billboard taxes, and restaurant taxes to local revenue (PAD) 2017-2021 are very lacking. The parking levy contribution for 2017-2021 is very less, for the 2017-2021 advertisement tax it is very less, and for the 20172021 restaurant tax it is very less contributing